Pemetaan Sebaran Habitat Dasar Perairan Laut Dangkal Menggunakan Citra Sentinel-2A di Teluk Gilimanuk - Putra, I Gusti Putu Bayu Arri; Putra, I Dewa Nyoman Nurweda; Putra, I Nyoman Giri (Journal of Marine and Aquatic Sciences; Vol 9 No 1 (2023), 2023)
West Bali National Park is a conservation area with such a high biodiversity. That includes mangrove forest, coastal, and shallow water ecosystem. As a conservation area, a distribution map of the shallow water habitat is necessary for decision making in the conservation’s benthic habitat developing program. One of the mapping method is remote sensing and requires Sentinel-2A Level 1C satelitte image. Sentinel-2A Level 1C is used due to its high resolution which is 10x10 meters for a single pixel. The aim for this research is for mapping the distribution of the shallow water habitat in Gilimanuk Bay while also assesses the accuracy of Sentinel-2A image. This research uses the Quantum GIS and SAGA GIS software to analyze the Sentinel-2A image. The image is transformed using Depth Invariant Index to reduce the scattering effect on the reflectance. After the image is being transformed by the Depth Invariant Index, it is classified using maximum likelihood method. The classification showed, the area of each classes are 56.59 hectares of corals, 18.01 hectares of seagrass, 128.97 hectares of waters, 45.76 hectares of mud sediment, 78.95 hectares of macro algae, and 26.67 hectares of sands. Overall accuracy assessment for this research calculated using confusion matrix and the result is 65.1% and considered good enough due to Coral Ecosystem Remote Sensing Data Analysis Guide by National Institute of Aeronautics and Space (LAPAN), in which the tolerance of the accuracy is 60%. Accuracy levels are influenced by number of classes, image resolution, class resemblance, turbidity, and seafloor material.